Examination and Optimization of a Heating Circuit for Energy‐Efficient Buildings. Issue 1 (9th December 2015) - Pöttgen, Philipp; Ederer, Thorsten; Altherr, Lena; Lorenz, Ulf; Pelz, Peter F.
Abstract: The conference center darmstadtium in Darmstadt is a prominent example of energy efficient buildings. Its heating system consists of different source and consumer circuits connected by a Zortström reservoir. Our goal was to reduce the energy costs of the system as much as possible. Therefore, we analyzed its supply circuits. The first step towards optimization is a complete examination of the system: 1) Compilation of an object list for the system, 2) collection of the characteristic curves of the components, and 3) measurement of the load profiles of the heat and volume‐flow demand. Instead of modifying the system manually and testing the solution by simulation, the second step was the creation of a global optimization program. The objective was to minimize the total energy costs for one year. We compare two different topologies and show opportunities for significant savings. Abstract : Global Optimization : The Zortström reservoir is the central component of heating in the darmstadtium. The conference center uses a biomass boiler and a district heating connection for its heat supply. We apply Technical Operations Research to find a better control and topology for the system. Discrete optimization techniques enable us to objectively rate and compare different topologies.